MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN - Ach. Faridul Ilmi Ach. Faridul Ilmi (Sociocouns: Journal of Islamic Guidance and Counseling, 2021)
The purpose of this study was to describe the characteristics of principal leadership, to describe the psychological characteristics of the principal’s leadership, and to design the leadership model of the principal in a psychological perspective. The research was conducted in Public Senior High School MAN 1 Jember. The research method used is qualitative research with case study design. Technique of data retrieval through interview, observation, and documentation. The data analysis used is interactive model analysis. The results show that the leadership characteristics shown by the principal are objective, democratic, friendly, humorous, honest, disciplined, assertive, able to control emotions, appreciate, motivate, have a family attitude to all members, fair, strong and religious. Based on the psychological characteristics of the principal’s leadership is a leader who shows the person calm, relaxed, patient, meticulous, not easily affected, and high self-awareness. Principal leadership models in psychological perspectives reflect a attribute sanguine and phlegmatic